Reinforcing carbon fixation: CO2 reduction replacing and supporting carboxylation. (February 2018) - Cotton, Charles AR; Edlich-Muth, Christian; Bar-Even, Arren
Graphical abstract: Highlights: Inorganic carbon can enter cellular metabolism via carboxylation or reduction. CO2 reducing enzymes can be as proficient as carboxylating enzymes. 'Reduction-first' pathways can support higher yield than carboxylation pathways. Carbon reduction and carboxylation can be integrated to enable new metabolism. The thermodynamics of CO2 reduction is a major challenge. Abstract : Carbon dioxide enters the biosphere via one of two mechanisms: carboxylation, in which CO2 is attached to an existing metabolite, or reduction, in which CO2 is converted to formate or carbon monoxide before further assimilation. Here, we focus on the latter mechanism which usually receives less attention. To better understand the possible advantages of the 'reduction-first' approach, we compare the two general strategies according to the kinetics of the CO2 -capturing enzymes, and the resource consumption of the subsequent pathways. We show that the best CO2 reducing enzymes can compete with the best carboxylases. We further demonstrate that pathways that fix CO2 by first reducing it to formate could have an advantage over the majority of their carboxylation-only counterparts in terms of ATP-efficiency and hence biomass yield. We discuss and elaborate on the challenges of implementing 'reduction-first' pathways, including the thermodynamic barrier of CO2 reduction. We believe that pathways based on CO2 reduction are a valuable addition to nature's arsenal for capturing inorganic carbon and could provide promising metabolic solutions that have been previously overlooked.